Legal Protection To The Public Notary In Providing Information Before The Investigation - Hanif Dzaki; Lathifah Hanim (Jurnal Akta, 2018)
A Notary is a Public Officer authorized to make an Authentic Agreement which has other powers as regulated in UUJN or under any other Law. Authentic Agreement aims to be used as powerful or perfect evidence if there is any occurrence of a dispute between the parties or there is a lawsuit from the parties. The method used in this study was sociological juridical method with descriptive analytical research specification, while the data analysis method used qualitative analysis. Based on the results of research and discussion, it can be concluded that the legal protection to the Notary in conducting a call by the investigator is conducted through the process in accordance with applicable legislation. Notary's call by the investigator shall be made with the prior approval of the Notary Honorary Council. It is as regulated in Article 66 UUJN. Other forms of legal protection that can be granted to a Notary are by supervision, attaching fingerprints and legal protection provided by the Indonesian Notary Association as the sole organization of Notary in Indonesia. Constraints faced by the Notary in executing summoning by the investigator are, the calling process which requires a long process and must be through the priority of the Notary Honorary Council in advance resulting in less effective time. So the solution is to conduct a more effective investigation by doing a good cooperation between the investigators, Notaries, Notary Honorary Council, and the Indonesian Notary Association.Keywords: Legal Protection; Public Notary; Agreement; Investigator